2022
DOI: 10.1007/s10479-022-05151-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel deep neural network model based Xception and genetic algorithm for detection of COVID-19 from X-ray images

Abstract: The coronavirus first appeared in China in 2019, and the World Health Organization (WHO) named it COVID-19. Then WHO announced this illness as a worldwide pandemic in March 2020. The number of cases, infections, and fatalities varied considerably worldwide. Because the main characteristic of COVID-19 is its rapid spread, doctors and specialists generally use PCR tests to detect the COVID-19 virus. As an alternative to PCR, X-ray images can help diagnose illness using artificial intelligence (AI). In medicine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 56 publications
0
11
1
Order By: Relevance
“…Again, our mean error values are far better than those obtained in 25 . Again, our results contradict the results in 24 where SARIMA and ARIMA were used for forecasting. Just like in 25 , our mean error values were far better than those obtained in 24 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Again, our mean error values are far better than those obtained in 25 . Again, our results contradict the results in 24 where SARIMA and ARIMA were used for forecasting. Just like in 25 , our mean error values were far better than those obtained in 24 .…”
Section: Discussioncontrasting
confidence: 99%
“…The results showed that the ARIMA model pointed to an increasing trend in USA, Spain, Germany, England, and France for the upcoming days. However, 24 used seasonal ARIMA (SARIMA) and ARIMA to model and forecast mpox cumulative cases for a short-term period, with the SARIMA model achieving the highest accuracy than the ARIMA model in modelling and forecasting confirmed and cumulative cases.…”
Section: Literature Reviews and Related Workmentioning
confidence: 99%
“…The pre-trained Xception model was selected in this work because it consumes few resources while maintaining acceptable accuracy, and its architecture is very easy to define and modify, making it a prime candidate for medical tasks [29]. It has been utilized in various medical tasks during the past two years, such as the assessment of benign and malignant gastric ulcer lesions based on gastrointestinal endoscopic images [30], the detection of COVID-19 from radiographic images [31], and the detection of knee osteoarthritis [32].…”
Section: Network Architecturementioning
confidence: 99%
“…A filter is produced for every channel of the given input data set to N using a single filter from the source channel to calculate kernel size RF × RF × N. It's calculated by the following Eq. ( 2) [25][26][27].…”
Section: Xception Modelmentioning
confidence: 99%